Lutzomyia longipalpis and the eco-epidemiology of American visceral leishmaniasis, with particular reference to Brazil - a review - Lainson, Ralph (2005)
Instituto Evandro Chagas. Departamento de Parasitologia. Belém, PA, Brasil.